Work, Employment, and Training through Africa-China Cooperation Zones: Evidence from the Eastern Industrial Zone in Ethiopia - Ding Fei (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
This paper by Ding Fei investigates the developmental impacts of Ethiopia's Eastern Industrial Zone (EIZ) through a cross-company and cross-sector analysis of local worker experiences of working for, training with, and learning from resident companies. It highlights both similarities and differences in Chinese companies' management strategies and training provisions, which are contingent upon industry sector, scale of production, and market conditions. While sixty percent of the surveyed local workers did receive training of varying quality and length, they were not satisfied with the training provision and promotion opportunities in current companies. The paper argues for concrete and targeted policy implementation by the Ethiopian government to enforce skills transfer by foreign investors, building of linkages between companies and local training institutions, and organizing zone-wide skills sessions.
Keywords: 330